Analisis Determinan Tax Avoidance pada Perusahaan Sub-Sektor Minyak, Gas, dan Batu Bara - Jessica Firda Aulia; Nuramalia Hasanah; Hera Khairunnisa (Teewan Journal Solutions, 2025)
This study is a quantitative study that aims to examine and analyze the influence of capital intensity, thin capitalization, foreign ownership, and audit committees on tax avoidance. The data used in this study is secondary data obtained from the financial reports of companies in the energy sector, specifically the oil, gas, and coal sub-sectors, listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The sample selection was conducted using purposive sampling based on specific criteria, resulting in a total of 38 company samples. Hypothesis testing was conducted using panel data regression analysis, with the support of EViews 13 software. The results of the analysis indicate that capital intensity and thin capitalization have a significant effect on tax avoidance. In contrast, foreign ownership and the audit committee do not have a significant effect on tax avoidance.